A Novel Pyridine and Julolidine Based Chemosensor for Al3+ Detection. Issue 11 (14th March 2023) - Zeng, Junzhu; Xu, Xin; Xue, Lei; Xu, Yang; Wang, Xin; Zhang, Yang; Wang, Haibin
Abstract: In this work, a pyridine and julolidine based chemosensor (L ) for Al 3+ with a turn‐on response in ethanol solution was designed and synthesized, whose emission intensity was enhanced by 85‐fold in the presence of Al 3+ by emitting bright green fluorescence at 480 nm. Meanwhile, the recognition process was hardly affected by other common cations. Based on the fluorescence titration data, the limit of detection (LOD) for Al 3+ was estimated to be as low as 2.74×10 −8  M. Job's plot ascertained the coordinate stoichiometric of L to Al 3+ as 1 : 1, with the association constant (Ka) of 7.24×10 3  M −1 depending on the Benesi‐Hildebrand equation. The combined effects of photoinduced electron transfer (PET) and excited state intramolecular proton transfer (ESIPT) were proposed as the plausible coordination mechanism of L toward Al 3+ . Moreover, the application ability of L for determination of Al 3+ was evaluated in water samples and with test strips. Abstract : A novel pyridine and julolidine based chemosensor for Al 3+ detection was developed. The chemosensor exhibited "turn‐on" response towards Al 3+ by emitting bright green fluorescence at 480 nm with detection limit of 27.4 nM. Moreover, the chemosensor could be effectively applied in detection of Al 3+ with test strips and in real water samples.